Analisis Pertumbuhan Laba Terhadap Nilai Perusahaan - Hasibuan, David HM (STIE Kesatuan, 2009)
Financial management objective is to maximize shareholder wealth by increasing firm value is intrinsic value and market value of the company. To achieve the objectives of financial management of premises ways to increase profits. With the increase in profit every year mean that these companies experienced profit growth. With the increase in corporate profit growth will increase the corporate value that is also an intrinsic value and market value of the company. Intrinsic value is the fair value of stock based on company financial performance. While the value of the stock market is the stock price prevailing in the market. The purpose of this study was to determine the effect of profit growth, as measured by net profit growth per year towards its intrinsic value as measured by the earning multiplier and market value, as measured by stock market price. This research was conducted from 2006 until the year 2010, by taking a sample of two companies namely PT Indofood Sukses Makmur, Tbk and PT Mayora Indah, Tbk. Based on the analysis, changes in profit growth at PT Indofood Sukses Makmur, Tbk has increased the impact on the intrinsic value and market value of the company from 2009 until 2010. It was indicated where in 2006 to 2007, 2007 to 2008, and 2008 to 2009 changed in profit growth can not increase the intrinsic value and market value of the company. The profit growth of PT Mayora Indah, Tbk has increased the impact on the intrinsic value and market value of company. It was indicated where in 2006 to 2007 changed profit growth will support improvements to the intrinsic value which was followed by an increase in market value in the year 2006 to year 2007. In 2008 to 2009, the profit growth value changes in return on equity resulting in increased impact on increasing the intrinsic value of which is followed by an increase in market value of PT Mayora Indah, Tbk. This was also seen in 2009 to 2010, the value of profit growth PT Mayora Indah, Tbk has increased the impact on the intrinsic value and followed with increased market value from 2009 to 2010. Only in 2007 to 2008 changed in profit growth can not enhance the intrinsic value and market value of the company. The result of calculation at the two firms are profit growth of PT Mayora Indah, Tbk, which have an impact to the intrinsic value and market value is better than the profit growth which affects to the intrinsic value and market value of PT Indofood Sukses Makmur, Tbk.